Ubezpieczenia od kradzieży ruchomych zabytków kultury z ekspozycji stałej w Polsce - Wieteska, Stanisław (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
Insurance coverage is one of the methods of providing security for movablecultural property. The article discusses the scale of theft of such objects in Polandand methods of valuation for the purposes of determining the sum of insurance.